Pyrazolo[4, 3‐h]quinoline Ligand‐Based Iridium(III) Complexes for Electrochemiluminescence. Issue 13 (6th June 2017) - Hsu, Chien‐Wei; Longhi, Elena; Sinn, Stephan; Hawes, Chris S.; Young, David C.; Kruger, Paul E.; Cola, Luisa De
Abstract: Electrochemiluminescence (ECL) based on [Ru(bpy)3 ] 2+ systems is widely utilized for immunoassays. In order to extend the promising potential of ECL‐based applications, Ir III complexes have recently attracted attention as probes because of their excellent luminescent properties and tunable emission wavelength. Here we describe a series of Ir complexes using a large π‐conjugated ligand and different ancillary chelates. The complexes synthesized have been chemically and spectroscopically characterized and used for ECL measurements with annihilation and co‐reactant methods. One of the Ir III complexes investigated exhibits the brightest, ever reported, ECL efficiency in acetonitrile employing the benzoyl peroxide (BPO) co‐reactant method. Abstract : I am a superstar ! A series of neutral luminescent Ir III complexes were synthesized and their spectroscopic behavior investigated. ECL measurements with annihilation and co‐reactant methods showed that one of them exhibits the brightest ECL efficiency, 6 times higher than Ru(bpy)3 2+, in acetonitrile employing the benzoyl peroxide (BPO) co‐reactant method.